Razvoj balinanja na evropskih in svetovnih prvenstvih od leta 1998 do leta 2011 - Borčnik, Aleš (Šport (Ljubljana), 2016)
The purpose of the paper was to establish the way the bocce volo disciplines (progressive throw, progressive throw in pairs, precision throw, circle, individual, pairs) developed at the European and World Championships from 1998 to 2011. The focus of attention was paid to the results achieved in the different stages of the competitions in the disciplines of progressive throw, progressive throw in pairs, precision throw and circle. Analysed were the number of throws and hits in both disciplines of progressive throw, and the number of points needed to achieve a certain result in the three disciplines of throw and the circle. The analysis was concentrated on the number of participants in each discipline at the European and World Championships. Moreover, presented are countries which got medals at the European and World Championships in all six disciplines in the analysed period. In addition explored is possibility that bocce vole would become a part of the programme for the summer Olympic Games.
Keywords: balinanje; bocce volo; development of the results; european championships; evropsko prvenstvo; olimpijske igre; olympic games; razvoj; rezultati; sport; svetovno prvenstvo; šport; world championships